Geologia, petrografia e geoquímica das rochas metavulcânicas ácidas da Estrada Real, Rio de Contas (BA) - Santos, Josiene Maria de Almeida (2017)
The studied acid metavolcanic rocks outcrop at Estrada Real, Rio de Contas (BA), SW of Bahia State. Those rocks represent the Novo Horizonte Formation, basal portion of Rio dos Remédios Group (Espinhaço Supergroup) and are associated to development of sin-rift phase at Oriental Espinhaço basin, at Chapada Diamantina. The methodology used to make this work consisted of fieldstrip, petrography and geochemistry. Twenty-one samples have selected to petrographic analyses and ten to whole rock chemical analyses. The rocks show grey to dark-grey color, are aphanitic and show incipient to well-marked foliation. Petrographically, the rocks present porphyroblastic, lepidoblastic and blast-porphyritic textures. The mineralogy consists of quartz blasto-porphyries, andaluzite and kyanite porphyroblasts, garnet pseudomorphs, feldspars, biotite, muscovite, sericite, chlorite, epidote, monazite, zircon and opaque minerals immersed in a quartz-feldspar matrix. The trace elements spiderdiagram shows enrichment of LILEs in relation to HFSEs. The negative anomalies of Sr, P, Nb-Ta and Ti are notable. The distribution patterns of the Rare Earth Elements show enrichment in ETRL in relation to ETRP and negative anomaly in Eu. It suggests the formation of these rocks in a continental rift environment, from a mantle previously modified by subduction.